Physical activity and selected correlates among adolescent school children aged 13 and 14 years in the Rathnapura District - Ranasinghe, R.D.S (My University, 2009)
Introduction Epidemiological studies conducted in both developed and developing countries have shown consistent results on health benefits of physical activity and health risk of inactivity leading to non communicable diseases. Very little research has been done on physical activity among children and adolescents and there is a paucity of information on physical activity level of Sri Lankan adolescents. Physical activity assessment questionnaires have been validated for adults. However, validated physical activity assessment instruments are not available in Sri Lanka to assess physical activity in adolescents. The present study was carried out with the objective of assessing the physical activity and sedentary behaviour pattern among adolescent school children aged 13-14 years in the Rathnapura district and identifying selected correlates of physical activity. The study included two phases. During Phase I of the study two study instruments were selected, modified and translated to assess the physical activity pattern, sedentary behaviour and physical activity correlates of adolescent school children aged 13-14 years in the Rathnapura district (PAQ-S and PACE+PSM-S). A questionnaire to collect socio demographic data of adolescents (PQPA-S) was also developed during phase 1. The P AQ-S was validated to assess the prevalence of physical activity among adolescent school children during Phase 1 of the study. Yam ex Digi-Walker CW 701 pedometer was used as the objective measure in validating the PAQ-S. Reliability of PAQ-S and PACE+PSM-S were also assessed. The outcome measure of physical activity assessment questions was participation in moderate to vigorous physical activity for at least 60 minutes per day for 5 days or more per week. Based on this cut off value adolescents were categorized as sufficiently active or insufficiently active. A cross sectional study was carried out during Phase 2 of the study to assess the physical activity pattern, sedentary activities and to identify selected environmental, socio-demographic and psychosocial correlates of physical activity pattern of adolescent school aged 13-14 years children in the Rathnapura district. The students were selected for the study using two stage cluster sampling technique. Socio demographic factors such as age, sex, sector, BMI, income level of family, social status of family, parental education level and parents physical activity level, functional classification of schools.